RELATIONSHIP OF BLOOD GLUCOSE LEVELS WITH USE OF HORMONAL CONTRACEPTION IN PUSKESMAS KOTA BARAT - Sri Rahma Amanda Sadingo; Titin Dunggio; Erfan AR. Lainjong (LP2M Universitas Bina Mandiri Gorontalo, 2021)
Injectable hormonal contraceptives contain the hormone progesterone which can cause adverse side effects for the wearer. The hormone used can affect the work of insulin in sugar metabolism as a result of which insulin becomes resistant. Insulin resistance causes the glucose levels that enter the body's cells to decrease as a result of which glucose remains in the blood vessels which results in high glucose levels in the body. West city health center has increased diabetes sufferers. According to data obtained from the Gorontalo City Health Office, there were 111 DM patients recorded at the West City Health Center in 2017, in 2018 there were 110 people and in 2019 there were 125 people. The purpose of this study was to determine the relationship between blood glucose levels and the use of injectable hormonal contraceptives at Puskesmas Kota Barat. This research is an analytic observational research with a quantitative approach method. The sample used was 30 patients with simple random sampling technique. The results of the study were found that 40% experienced an increase in blood glucose levels and as much as 60% were in the normal category. Based on the results of the examination, it can be concluded that there is no relationship between blood glucose levels and the use of injectable hormonal contraceptives p = 0.617 (α> 0.05). This is because most of the patients are in the productive age category and the duration of using injection contraception is <10 years.